PENDAMPINGAN USAHA PANGAN OLAHAN SUSU TENJOMILK DESA TENJOLAYA KABUPATEN BANDUNG - Nanda Ravenska; Pranandiva Dwi Asri N A; Dewi Ambarwati; Ariana Nashya Sandi P; Nadia Yulianti; Yuniar Daniati (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2023)
Tenjolaya Village is one of the villages in Bandung Regency as a contributor to fresh cow's milk from dairy cattle. The Tenjolaya Village breeder group has a large volume of cow's milk but has not been able to optimally manage livestock products which can be sold at a higher selling price. One of the efforts to optimize livestock production in the form of fresh cow's milk is by processing it into dairy food products. The Business Incubator Center (Bicube) Politeknik STIA LAN Bandung provides business assistance for the people of Tenjolaya Village so that they can optimize the utilization of fresh cow's milk. The method of implementing the assistance activities consists of two stages, namely the preparation and business assistance stages. The results of business assistance activities include the TenjoMilk trademark, NIB, PIRT permit, packaging design, email and social media accounts, as well as product selling price estimation. These business assistance activities enable the community to independently produce higher quality and competitive dairy products which can be an alternative for earning income and improving the welfare of the people of Tenjolaya Village.